Monitoring and evaluation of hypotension in the extremely preterm - Ping, Ping; Yu, Beimeng; Xu, Renjie; Zhao, Pingping; He, Shuqi (Frontiers in Cardiovascular Medicine, 2024)
With the development of neonatal medicine, more and more extremely preterm infants have been treated. How to deal with hypotension is a big challenge for neonatologist in the process of diagnosis and treatment. The lack of uniformity in the definition of hypotension, challenges in measuring blood pressure accurately, and insufficient consistency between digital hypotension and hypoperfusion are the primary causes. How to check for hypotension and monitor blood pressure is thoroughly explained in the article. To give neonatologists a resource for the clinical management of hypotension in extremely preterm.